ANALISIS FDR DAN BOPO YANG MEMPENGARUHI NPF (Studi Kasus Pada Bank Umum Syariah Tahun 2015-2020) - rivaldy, yoga (COMPETITIVE, 2023)
The purpose of this research is to determine the effect of FDR and BOPO on ROA. Quantitative method is used as a method in this research. The population in this study consisted of 14 Islamic Commercial Banks and used Perposive Sampling sampling technique. Obtained a sample of 5 banks. This research gives the result that is. For the simultaneous f test that NPF can be affected by FDR and BOPO. The t-test shows that NPF cannot be affected by FDR but NPF can be significantly affected by BOPO. Keywords : FDR, BOPO and NPF